2012
DOI: 10.1155/2012/173527
|View full text |Cite
|
Sign up to set email alerts
|

Failed Weaning from Mechanical Ventilation and Cardiac Dysfunction

Abstract: Failure to transition patient from controlled mechanical ventilation to spontaneous breathing trials (SBTs) in a timely fashion is associated with significant morbidity and mortality in the intensive care unit. In addition, weaning failures are common in patients with limited cardiac reserves. Recent advances in cardiac echocardiography and laboratory measurement of serum biomarkers to assess hemodynamic response to SBT may provide additional information to guide clinicians to predict weaning outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 51 publications
1
11
0
2
Order By: Relevance
“…In the present study, there was statistically highly significant relation between presence of ischemic heart diseases and SBT outcome (P=0, 000), which matches with the results of Ghoneim et al 14 In the present study there was statistically significant relation between left ventricular ejection fraction (EF%) (P =0.001), left ventricular diastolic dysfunction (P = 0.000), right ventricle systolic pressure (RVSP) (P <0.001) and SBT outcome. 15 This agrees with the results of Porhomayon et al, 16 that showed that ischemic heart disease and systolic or diastolic dysfunction contributes to increase in cardiac load and weaning failure. Extra demand on cardiac working load imposed by SBT may become apparent when transferring patient from positive to spontaneous ventilation.…”
Section: From the Present Study The Following Results Were Obtainedsupporting
confidence: 91%
“…In the present study, there was statistically highly significant relation between presence of ischemic heart diseases and SBT outcome (P=0, 000), which matches with the results of Ghoneim et al 14 In the present study there was statistically significant relation between left ventricular ejection fraction (EF%) (P =0.001), left ventricular diastolic dysfunction (P = 0.000), right ventricle systolic pressure (RVSP) (P <0.001) and SBT outcome. 15 This agrees with the results of Porhomayon et al, 16 that showed that ischemic heart disease and systolic or diastolic dysfunction contributes to increase in cardiac load and weaning failure. Extra demand on cardiac working load imposed by SBT may become apparent when transferring patient from positive to spontaneous ventilation.…”
Section: From the Present Study The Following Results Were Obtainedsupporting
confidence: 91%
“…Our available results were similar to the results from other domestic and overseas studies. Other studies have indicated that after statistical adjustment for disease conditions, underlying diseases and age, weaning failure remains an independent risk factor for predicting in-hospital mortality [19] . Additionally, weaning failure exacerbates the deterioration of underlying diseases and complications, such as aspiration, atelectasis and even pneumonia [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to determine SBT along with NT-proBNP as criteria for extubation, the value of elective NT-proBNP levels is crucial and needs a balanced approach to avoid 4 Two of 63 infants who passed SBT were excluded from further data analysis due to laryngeal dyspnea. 5 NT-proBNP ! 18,500 pg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…However, almost 22–28% of preterm neonates will have difficult or delayed ventilator weaning with the risk of a higher complications, including morbidity and mortality . Weaning failure is usually defined as the failure of the spontaneous breathing trial (SBT), or the need for reintubation during the 48 hr after extubation . Reintubation not only increases the risk of aspiration and nosocomial pneumonia, but also impacts the developmental outcome of preterm infants with high morbidity and mortality of retinopathy of prematurity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation